An Experimental Study on the Effect of Shape and Location of Vortex Generators Ahead of a Heat Exchanger - Wisam Abed Kattea (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
An experimental study is carried out on the effect of vortex generators (Circular and square) on the flow and heat transfer at variable locations at (X = 0.5, 1.5, 2.5 cm) ahead of a heat exchanger with Reynolds number ranging from 62000< Re < 125000 and heat flux from 3000 ≤ q ≤ 8000 W/m2 .